The interplay between microbiota and brain-gut axis in epilepsy treatment - Zhu, Hanxiao; Wang, Wei; Li, Yun (Frontiers in Pharmacology, 2024)
The brain-gut axis plays a vital role in connecting the cognitive and emotional centers of the brain with the intricate workings of the intestines. An imbalance in the microbiota-mediated brain-gut axis extends far beyond conditions like Irritable Bowel Syndrome (IBS) and obesity, playing a critical role in the development and progression of various neurological disorders, including epilepsy, depression, Alzheimer’s disease (AD), and Parkinson’s disease (PD). Epilepsy, a brain disorder characterized by unprovoked seizures, affects approximately 50 million people worldwide. Accumulating evidence suggests that rebuilding the gut microbiota through interventions such as fecal microbiota transplantation, probiotics, and ketogenic diets (KD) can benefit drug-resistant epilepsy. The disturbances in the gut microbiota could contribute to the toxic side effects of antiepileptic drugs and the development of drug resistance in epilepsy patients. These findings imply the potential impact of the gut microbiota on epilepsy and suggest that interventions targeting the microbiota, such as the KD, hold promise for managing and treating epilepsy. However, the full extent of the importance of microbiota in epilepsy treatment is not yet fully understood, and many aspects of this field remain unclear. Therefore, this article aims to provide an overview of the clinical and animal evidence supporting the regulatory role of gut microbiota in epilepsy, and of potential pathways within the brain-gut axis that may be influenced by the gut microbiota in epilepsy. Furthermore, we will discuss the recent advancements in epilepsy treatment, including the KD, fecal microbiota transplantation, and antiseizure drugs, all from the perspective of the gut microbiota.